DEVELOPMENT OF REGIONAL LOGISTICS CENTERS AS A DIRECTION OF ENTREPRENEURSHIP IMPROVEMENT - GONCHAR, Olga; KASII, Lesiya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The use of logistics tools for the organization and improvement of business activities in any branch of the economy under the conditions of the global challenges of our time are becoming a vitally necessary strategy. Considering the magnitude of the destruction and the need to rebuild our economy after the war, the formation of logistics centers in Ukraine will be a solid foundation in terms of saving resources, time and human effort. In certain regions, such a need arose even before martial law, so now its importance is growing many times over. Using the example of the Lviv region to optimize the circulation of goods between individual subjects of the agricultural sector and strengthen close economic cooperation with transport and logistics companies, we proposed to form a logistics distribution center and illustrated the effectiveness of its functioning. The development of the agricultural sector involves the implementation of a systemic approach based on the combination of production, distribution and storage of certain types of agricultural products. Under such conditions, it is logistics that acts as a powerful tool for increasing the efficiency of activity, as it allows optimizing the movement of agricultural products from the producer to the consumer. And the efficiency and safety of product transportation depends on its quality and competitiveness and, accordingly, the financial results of all agricultural market entities. The article presents the results of research on the prospects of formation and substantiates the need for the development of a regional logistics distribution center on the example of the Lviv region (districts - Sambirskyi, Starosambirskyi, Drohobytskyi). The necessity and expediency of forming a similar logistics center for farms and individual households engaged in the cultivation of fruit and vegetable products and other subjects of the logistics sector that join the chain of goods movement is substantiated. The formation of the regional logistics center of distribution is projected on the basis of the cooperation of subjects of the rural agricultural sector with transport and logistics companies of the region. This will allow agricultural producers to significantly save resources and time for the distribution of products and will create additional opportunities for increasing the volume of products and improving the quality of their processing, storage and delivery to end consumers. It will also create real opportunities for the export of high-quality fruit and vegetable products, as natural products grown on Ukrainian soil.